Data for paper 'Identifying and characterising the impact of excitability in a mathematical model of tumour-immune interactions' - Osojnik, A; Byrne, H; Gaffney, E (University of Oxford, 2020)
Please see included 'README.md' for details on the dataset. Data were produced using Python and Mathematica.